Roman Pollak jako badacz renesansu - Meller, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article presents Roman Pollak’s research into the literature of the Renaissance, focusing primarily on the studies of Łukasz Górnicki’s Dworzanin (The courtier) and quoting Pollak’s own thoughts on his work voiced in his private correspondence.